Literature review: correlation of ari incidence to stunting - Andi Muthiyah A AM (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Stunting is a growth and development disorder experienced by children due to various risk factors, including poor nutrition, repeated infections, and inadequate psychosocial stimulation. ARI is one of the health problems that exist in developing and developed countries. This study aims to obtain an overview of the correlation of the incidence of ARI to the occurrence of stunting in children aged 12-60 months. The research method used is a literature review study, which is a comprehensive review of research that has been done before, where researchers look for several articles and journals that meet the criteria and are valid and accurate. Researchers then analyze the research data obtained and then take the essence of various relevant research data. Results: Based on information sources obtained from 16 articles from Indonesian and international journals in the 2011–2023-time frame. From previous research, it shows that there is a relationship between ARI and stunting in children. Other studies also show that the frequency of ARI events also has an influence, where the study shows that toddlers with ARI in the last two weeks have three times more risk of stunting than toddlers who in the last two weeks do not have a history of ARI. The correlation between the presence of ARI and the incidence of stunting is caused by an increase in metabolic needs and disruption of food intake that occurs during a child's illness. Inflammation that occurs due to ARI experienced by children can cause metabolic disorders in the body. It can be concluded that there is a correlation between acute respiratory infections and the incidence of stunting. The condition of ARI and body immunity in children under five has a close relationship that can have an impact on stunting